A German Perspective on Legal and Political Problems of Coalition Governments - von Münch, Ingo (Victoria University of Wellington Law Review, 1999)
In September and October 1998 Professor von Münch was a visiting fellow of the New Zealand Institute of Public Law. During an extremely busy visit, Professor von Münch gave a number of seminars on aspects of German Constitutional and Electoral Law. These seminars, given by both a leading Constitutional and Electoral Law academic and a former deputy prime minister of the State of Hamburg and former member of the Bundesrat, or German Senate, were timely given the trials and tribulations of New Zealand's first MMP Coalition Government which had then just ended in the sacking of the minor party's leader as Deputy Prime Minister. In contrast to much of the contemporary gloom at the perceived failed hope of MMP, Professor von Münch presented a hopeful view of both the electoral system that New Zealand had imported from Germany and of the possibilities of Coalition Government. The following is an enlarged text of a speech, delivered to the Public Law section of the New Zealand Ministry of Justice.